Prostate cancer in transgender women: what does a urologist need to know?. (21st July 2021) - Bertoncelli Tanaka, Mariana; Sahota, Kirpal; Burn, James; Falconer, Alison; Winkler, Mathias; Ahmed, Hashim U.; Rashid, Tina G.
Abstract: Objective: To review of the existing literature, current guidelines and standard of practice related to prostate cancer in transgender women, as the transgender population share many of the same healthcare needs as their cisgender counterparts, but may have additional specialist needs. Materials and methods: We performed a non‐systematic review of the literature, current guidelines and standard of practice related to prostate cancer in transgender women. Results: Our search revealed 10 case reports of prostate cancer in transgender women, four specialist opinion papers, six cohort studies, and four systematic reviews. The information in these publications were assimilated to produce a review of prostate cancer in transgender women. Conclusion: The risk of prostate cancer in transgender women who are not on gender‐affirming hormone therapy (GAHT) or who have not had gender‐affirming surgery (GAS) and gender non‐conforming individuals (who may never commence GAHT or have GAS) is the same as that in the cis male population. In these patients, healthcare professionals need to be able to discuss screening, diagnostic and treatment options considering future wishes for gender‐affirming treatment. Prostate cancer incidence in transgender women on GAHT or following GAS is lower than age‐matched cis‐male counterparts, but diagnosis and treatment is more nuanced. The present review discusses the existing literature about development and incidence of prostate cancer in this population, and makes recommendations about screening, the usefulness of diagnostic tools e.g. prostate‐specific antigen and magnetic resonance imaging, and considerations when formulating treatment. Potential directions for future research are discussed, which will hopefully lead to development of robust evidence‐based guidelines for the diagnosis and management of prostate cancer in transgender women.